2021
DOI: 10.3934/publichealth.2021057
|View full text |Cite
|
Sign up to set email alerts
|

The underlying mechanisms for severe COVID-19 progression in people with diabetes mellitus: a critical review

Abstract: <abstract> <p>Diabetes mellitus (DM) has a high incidence of comorbidities among patients with severe coronavirus disease 2019 (COVID-19). The elevated prevalence of DM in the world population makes it a significant risk factor because diabetic individuals appear to be prone to clinical complications and have increased mortality rates. Here, we review the possible underlying mechanisms involved in DM that led to worse outcomes in COVID-19. The impacts of hyperglycemia side effects, secondary comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 186 publications
1
4
0
Order By: Relevance
“…Multi-factor linear regression analysis showed that the occurrence of the disease, that is, its manifestation, is, besides HRC, significantly affected by the combinations of RFs: hypertension and hyperlipidemia; hypertension and DMT2; hyperlipidemia and smoking. These findings are in agreement with other research suggesting the significant RFs for COVID-19—hypertension, hyperlipidemia, and DMT2 ( Figueroa-Pizano et al, 2021 ; Kuo et al, 2020 ; Velavan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multi-factor linear regression analysis showed that the occurrence of the disease, that is, its manifestation, is, besides HRC, significantly affected by the combinations of RFs: hypertension and hyperlipidemia; hypertension and DMT2; hyperlipidemia and smoking. These findings are in agreement with other research suggesting the significant RFs for COVID-19—hypertension, hyperlipidemia, and DMT2 ( Figueroa-Pizano et al, 2021 ; Kuo et al, 2020 ; Velavan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…There is evidence that the same RFs are significant comorbidities for COVID-19 ( Yamamoto et al, 2021 ). On the other hand, cardiovascular disease and diabetes were identified as major RFs for severe COVID-19 in older individuals ( Figueroa-Pizano et al, 2021 ; Velavan et al, 2021 ). We also examined the distribution of ABO blood groups among patients and controls, as well as the frequency of HRC within each blood group.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence points towards a greater risk of more severe COVID-19 outcomes in individuals with T2D and obesity, two frequently co-existing conditions [41][42][43]. As a routinely used medication in T2D, metformin has not only a hypoglycemic activity, but also impacts the gut microbiome by enhancing the SCFAs levels, which harbor antiinflammatory activity [44].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic inflammatory condition in T2D is considered the underlying mechanism for the “cytokine storm” complication and worsens the outcomes of COVID-19 [ 160 ]. It is assumed that hyperinflammation may result in multiorgan failure, a general complication in critical COVID-19 cases [ 161 ].…”
Section: Immunoregulation Gut Microbiota and Covid-19mentioning
confidence: 99%